Identifikasi Potensi Pembentukan Air Asam Tambang Batubara (PAF /NAF) dengan Menggunakan Metode Uji NAPP (Net Acid Producing Potential) - Baskara Widy Artyanto Putro; Diyan Parwatiningtyas (Universitas Indraprasta PGRI Jakarta, 2019)
Several laboratories tests have been developed in Indonesia and another countries that carry out mining activities, especially coal mining. The purpose of this analysis is to find out the presence and absence of soil layers which have the potential to form acidity. The most commonly known analytical methods are static and kinetic methods. The most commonly known method of analysis is static and kinetic methods. Our test this time are uses the NAPP method (Net Acid Producing Potential).Aand then, from the results of this calculation, was known that the mine area had acidic or not. This time, an investigation was conducted to determine the acidity of PAF (Potential Acid Forming) and NAF (Non Acid Forming), which is owned by the mining company PT GIE (Globalindo Inti Energy) at the Handil, Muarajawa, Balikpapan, East Kalimantan regions. From the results of tested and mapped , it was found that this mining area had NAF (Non Acid Forming) soil content, with a PH range between 4.65 - 5.75 and had a negative NAPP price.